Dance-based body-movement as kinesthetic therapy to reduce the impact of Prolonged Periods Classroom Settings Algerian Primary School - Zerf, Mohammed (World News of Natural Sciences (WNOFNS), 2019)
In recent years, Dance-based body-movement regulated video games are subject as advance programs school-based physical health activity. Assumed in European primary school to help schoolchildren to obtain a better health-related Classroom Settings. Stimulated the case of Greece Primary School to covers aspects of physical, emotional, social, and mental functioning and well-being. Looks at the correlation between movement and emotion, this study was to investigate the significance of Play Dance and its impact on Based-School Algerian Primary School. Declared by the dance psychotherapeutic studies as support to increase the intellectual, emotional, and motor functions of the body. For purposed, a four-week educational intervention in the field of dance was implied during school recess (morning and afternoon). Accounted as 10 minutes physical daily activity administers in the form imitating dance moves basing on Freeze Game (Just Dance Kids 2014) modal. The sample consisted of 45 male scholars’ 4’-class, primary slimani school residence of Naama, municipality of Mecheria. Test before and after the invested program based on battery INDARES. Data analysis was performed based on descriptive statistic indices, Paired Samples Correlations, and Paired Samples Test. The results showed differences between the start and end of the educational intervention. Its recommendation provides very high-grade results with considerable physiological and motor children improvements correlated children overall health, in particular under Algerian primary school guidance system that lessen the time of physical activity appreciated as inconsistent with academic children progress in this age school.
Keywords: Play dance; health-related quality of life; Algerian primary school